2017
DOI: 10.21767/2471-8300.100024
|View full text |Cite
|
Sign up to set email alerts
|

Tear and Pterygium: A Clinico-Pathological Study of Conjunctiva for Tear Film Anomaly in Pterygium

Abstract: Aims: To evaluate the clinical and histological status of tear film in patients with unilateral pterygium. Settings and Design:Cross-sectional, case-control, doubleblinded study. Methods and Material:Cross-sectional study of both eyes of 102 patients with unilateral pterygium was conducted between March 2011 to December 2012. Patients were subject to fluorescein lower tear meniscus height (LTMH) evaluation, fluorescein tear break-up time (TBUT), Schirmer's test (using topical anesthetic), vital staining (viz. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It follows that the tear film quantitation is changed in the pterygium eyes. Onkar et al[21] also demonstrated that the TMH, measured using OCT, was significantly lower in eyes with pterygium than in control eyes. They reported that 90.2% of pterygium eyes showed abnormal TMH, which was a higher proportion than in our study, although they considered a TMH value <0.3 mm, rather than <0.22 mm, to be abnormal, so the different result was likely due to the cutoffs used to define abnormal TMH.…”
Section: Discussionmentioning
confidence: 99%
“…It follows that the tear film quantitation is changed in the pterygium eyes. Onkar et al[21] also demonstrated that the TMH, measured using OCT, was significantly lower in eyes with pterygium than in control eyes. They reported that 90.2% of pterygium eyes showed abnormal TMH, which was a higher proportion than in our study, although they considered a TMH value <0.3 mm, rather than <0.22 mm, to be abnormal, so the different result was likely due to the cutoffs used to define abnormal TMH.…”
Section: Discussionmentioning
confidence: 99%
“…After several blinks, the patient avoids blinking and the tear film is examined using a broad-beam of slit lamp with a cobalt blue filter. (4) Tear Breakup Time (TBUT) is the time interval between a complete blink and the appearance of the first break, discontinuity or dry spot observed in the tear film. (5) TBUT less than 10s suggest an abnormal tear film (6) , with values of 5s to 10s, considered marginal, and less than 5s, indicative of dry eye symptoms.…”
Section: Introductionmentioning
confidence: 99%